Practices and Challenges of Continuous Assessment in Colleges of Teachers Education in West Oromia Region of Ethiopia - Gemachu Oli; Teklu Tafase Olkaba (STKIP Singkawang, 2020)
The main purpose of this study was to investigate the practices and challenges of continuous assessment in colleges of teachers’ education in western Oromia region. For this study, the researchers selected three colleges of teachers education purposely based on the job experience. The researchers selected Nekemte, Dembi Dollo and Shambo colleges teachers education from well, medium, lower experienced respectively. A descriptive survey design involving both qualitative and quantitative approaches was employed. 134 student-teachers and 178 college teachers were selected and participated in the study. The quantitative data was collected through a questionnaire and observation checklist and analyzed using frequency and percentage, whereas, the qualitative data interview and document analysis were analyzed using the narrative form and interpretative way. The finding of the study revealed that the extent of practicing continuous assessment in class is low. The study also showed that teachers have positive perceptions toward continuous assessment and they accepted continuous assessment as important to improve the achievement of learners. The finding disclosed that large class size, shortage of time, teachers workload, the low interest of students, large instructional content, and lack of commitment among teachers as the major factors hindering the practice of continuous assessment in colleges of teachers education. The researchers recommend that educational authorities and stockholders should make effort to students per class to manageable numbers, College administrators should allow teachers to cover the minimum workload than overloading above the standard set for the college of teachers education.